ANALISIS KETERAMPILAN GURU AGAMA BUDDHA DALAM MELAKUKAN EVALUASI PEMBELAJARAN DI SEKOLAH DASAR (SD) NEGERI 3 SOKARAJA - Diyanti; Widodo, Urip; Putranto, Dwiyono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research was conducted in order to analyze the skills of Buddhist teachers in conducting learning evaluations at SD Negeri 3 Sokaraja, to describe the process of implementing learning evaluations carried out by Buddhist teachers at SD Negeri 3 Sokaraja. This research uses descriptive qualitative research. Through in-depth exploration of Teacher Skills in Learning Evaluation at SD Negeri 3 Sokaraja, data collection in this research used observation, interview and documentation techniques. The research subjects were Buddhist education teachers, Buddhist students, and the principal at SD Negeri 3 Sokaraja. The research results show that early stage teachers need to understand the concept of assessment such as the definition of assessment, objectives, functions, principles and types. Teacher competency in evaluation activities includes evaluation program planning, evaluation program design, evaluation program development, evaluation program implementation and evaluation. In the evaluation process itself, teachers must be able to plan and carry out evaluations, process data, write reports, and use evaluation results.